Teacher’s Strategy in Fostering a Law Awareness Refinement in School - Pettalongi, Adawiyah; Datumula, Sarfika; Nurmala, Ma'rifah (STKIP Yapis Dompu, 2022)
Teachers have an essential role after side of parents in fostering students' legal awareness of school rules. The role of teachers in this case has been carried out by means of socialization, with the aim of providing knowledge to students of the existence of school rules, considering that as the indicators of legal awareness and it refinement, students need the knowledge conceptually where there are several actions in the school environment that are regulating by law in the form of school rules. Teachers must also foster students' understanding of school rules. The teacher's action in this study is to explain the substance of the rules regulation in the school rules. Furthermore, the teacher fosters students' attitudes towards school discipline, the role of teachers in fostering students' attitudes towards school discipline begins with the implementation of school discipline where in the implementation and enforcement of school discipline the teacher has been carried out if there is a violation of school discipline committed by students.